Czech enterprises and the multidivisional form: Legitimation, legacies and structural choice - Ed Clark (Journal for East European Management Studies, 1998)
This article examines the divisionalisation of organisational structures in three former state enterprises in the Czech Republic. The research findings suggest that this process has occurred in three broad phases and that structural change in the three enterprises has exhibited both common and divergent patterns. While considering the role of economic and institutional factors in the explanation of these different pathways, the main argument focuses on management motives behind the structural choices made, the socio-political responses to those choices from other social actors, and the significance of pre- 1989 organisational legacies. – – Der vorliegende Artikel untersucht die Divisionalisierung dreier früherer Staatsbetriebe in der Tschechischen Republik. Die Untersuchungsergebnisse zeigen drei wesentliche Phasen der Umstrukturierung. Der Prozeß der Strukturveränderung in den drei Unternehmen weist sowohl Gemeinsamkeiten als auch Unterschiede auf. Bei der Erklärung dieser unterschiedlichen Transformationspfade werden ökonomische wie auch institutionelle Faktoren berücksichtigt. Die wesentliche Argumentation konzentriert sich aber auf entscheidungsbeeinflussende Motive des Managements, die Reaktion anderer gesellschaftlicher Kräfte auf diese Entscheidungen und die Bedeutung organisationaler Regelungen vor 1989.
Keywords: 650